2010
DOI: 10.3354/dao02265
|View full text |Cite
|
Sign up to set email alerts
|

Detection of salmonid alphavirus RNA in wild marine fish: implications for the origins of salmon pancreas disease in aquaculture

Abstract: Salmonid alphaviruses (SAVs), which include the aetiological agents of salmon pancreas disease (SPD) in farmed Atlantic salmon Salmo salar L. and sleeping disease (SD) in rainbow trout Oncorhynchus mykiss (Walbaum), are significant viral pathogens of European salmonid aquaculture. SAV is horizontally transmitted and the virus can survive for extended periods in seawater. A lack of convincing evidence for vertical transmission coupled to the fact that the SPD virus (SPDV) occurs in historically infected sites i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 23 publications
4
57
0
Order By: Relevance
“…The generally high Ct values re ported in the current study are indicative of a low level of viral RNA in heart tissue. This confirms and extends previous work that identified the presence of SAV RNA in heart and kidney tissue collected from flatfish in Scottish coastal waters, but which failed to isolate the virus (Snow et al 2010). Based on the presence of SAV in dab in a locality remote from salmonid aquaculture, we concluded that a reservoir of SAV in non-salmonid wild fish probably existed prior to the largescale development of salmonid aquaculture in Scotland (Nash 2011).…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…The generally high Ct values re ported in the current study are indicative of a low level of viral RNA in heart tissue. This confirms and extends previous work that identified the presence of SAV RNA in heart and kidney tissue collected from flatfish in Scottish coastal waters, but which failed to isolate the virus (Snow et al 2010). Based on the presence of SAV in dab in a locality remote from salmonid aquaculture, we concluded that a reservoir of SAV in non-salmonid wild fish probably existed prior to the largescale development of salmonid aquaculture in Scotland (Nash 2011).…”
Section: Discussionsupporting
confidence: 78%
“…A previous study using RT-qPCR detected a potential wild reservoir of SAV in several flatfish species, but failed to provide follow-up evidence in support of this result, e.g. successful isolation of the virus (Snow et al 2010). The objectives of the current study were (1) to determine the prevalence of SAV subtypes in common dab from Scottish and international waters, (2) to culture any identified SAVs in vitro and (3) to examine common dab tissues from selected sampling areas for the presence of histopathological changes consistent with pancreas disease.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations